The Influence of Information Technology and Tax Knowledge on the Application of E-Filling and its Impact on Tax Reporting - Rilo Muzani Syukur (Jurnal Impresi Indonesia, 2025)
This research was conducted at Public Health Centers (Puskesmas*) in Bandung Regency. Preliminary study results indicated that tax reporting optimization has not been achieved. This is suspected to be due to the low condition of Information Technology, Tax Knowledge, and the Application of e-Filing. The research aims to analyze the magnitude of the influence of Information Technology and Tax Knowledge on the Application of e-Filing, as well as its implications for Tax Reporting. Based on management theory, human resource management, information technology, and e-Filing theory, this quantitative research was conducted using a survey method. The population consisted of 62 people, with a sample of 36 people selected through Purposive Sampling. Data collection techniques employed questionnaires, interviews, observation, and documentation studies. The data analysis technique used was Path Analysis with the assistance of IBM SPSS 21.0 and Excel 2017. The results showed that partially, the influence of Information Technology on the Application of e-Filing was 31.03%, while the influence of Tax Knowledge was 30.86%. Simultaneously, both independent variables influenced the Application of e-Filing by 61.89%. As an implication, the Application of e-Filing was proven to have a significant and dominant influence on Tax Reporting, amounting to 86.31%. These findings confirm that a combination of technological support and human resource competence is key to driving the adoption of digital systems and improving the quality of tax reporting compliance in local government institutions